The EU maritime safety policy and international law (Nijhoff, 2008)
This book offers a comprehensive international law analysis of the European Union's maritime safety legislation. Acts of EU law since 1993 have been dealt with a variety of subjects, such as port State control, classification societies, vessel traffic management, ship construction, environmental protection and pollution sanctions. This legislation is analysed from the point of international law, notably the law of the sea and the international maritime conventions. The relationship between EU law and international law within the internal EU legal system is also analysed from the specific perspective of maritime safety law.
Includes index